Empowering student through a democratic classroom : a case study in a Malaysian public university - Lina Mursyidah Hamzah
This qualitative study aimed at using a democratic classroom approach to empower students’ thoughts. The study also explored the democratic classroom characteristics that can be established in Malaysian undergraduate classrooms. Case study method was used to gain an in-depth understanding of the real context. For this purpose, EDC 4365 course (Methods in Teaching Moral Education I) was selected to be the context of this study. The selection of participants in this study was done through purposive sampling. Semi-structured in-depth interviews were carried out on six voluntary students who had experienced a democratic classroom approach. Besides the interviews, twenty-two other students who shared similar experience also voluntarily offered their reflective journals that contain their feelings and perceptions towards the democratic classroom approach, particularly in terms of empowering their own thoughts. The data of the interviews were then transcribed and analysed and later, the emerging themes were categorised. As for the journals, the essays were coded accordingly. The findings of this study revealed five major themes. The first theme contains five characteristics of democratic classroom, which are respectful towards each other, meaningful learning, equality, freedom, and power sharing. The second theme is empowerment of thoughts, which emphasises on stimulating, improving critical thinking skills and enhanced creative thinking skills. The third theme is democratic environment which consists of classroom seating arrangement, student centred and democratic surrounding. The fourth theme is self-improvement where students feel enhanced confidence level, enhanced communication skills and improving manner. The final theme is challenges in implementing democratic classroom in terms of lecturers’ skills and their ability to handle dominant students. The findings of this study are also in line with Freire’s ideology on liberating education, which considers dialogue as the fundamental element in the classroom, as well as Dewey’s ideology on democratic education which encourages active learning. Therefore, this study possesses a crucial implication on the policy-makers who have the authority to change the teaching methods, particularly at the higher level of education. It enriches lecturers’ role at universities in adjusting their teaching methodologies to enhance students’ empowerment.